An analysis of traditional Ojibwe civil chief leadership - Flocken, Henry (2013)
University of Minnesota Ed.D. dissertation. May 2013. Major: Educational Policy and Administration. Advisor: Frank Guldbrandsen. 1 computer file (PDF); vi, 184 pages. Little is known about traditional Ojibwe civil chief leadership. This critical ethnography is an analysis of traditional Ojibwe civil chief leadership. Hereditary chiefs are interviewed. Chief leadership lies nested in the Anishinaabe Constitution. It is clan-based and value-based. It includes all of creation. Leadership is emergent and symbolic. Chiefs symbolized and are spokespersons for the will of the people. They were selected based on their virtues. The real power is in the people, in clans in council. Hunting groups had spokesmen in clans. Chiefs were chosen from the clan headmen in council. Larger area councils selected a chief from the chief-council. This system is spiritual, holistic, consensual, and egalitarian. It empowers the people. Colonial oppression has transformed what was a bottom-up structure to a Western top-down structure often filled with nepotism, favoritism, and corrupt and coercive leadership. Coupled with historic trauma, this engenders self-oppression and social dysfunction. Many activists call for a return to traditional Anishinaabe government, but little is known about what that is. The purpose of this critical ethnography is to know traditional Ojibwe civil chief leadership, add to leadership knowledge, and use that knowledge in Anishinaabe leadership models for tomorrow.